An Overview of Developed Forms of Pretend Play Situation in Ecec Institutions in Lithuania - Brandišauskienė, Agnė; Maslienė, Danguolė (Pedagogika, 2014)
This article aims to give an overview of the situation of children’s play in ECEC classrooms. According to the teacher’s opinions and observations, it could be said that ECEC institutions allow free play of children: the kids like to play in small-sized and often gender-mixed groups. It is observed that while playing alone girls and boys prefer different games, and each play theme is usually developed from a few days to a week. Deeper analysis reveals that the topics of children’s games are steaming from their personal experience. The older children more freely construct imaginary situations and are less dependent on objects and environment. In teacher’s opinions, fantasy themes (that are the indicators of higher level of play) of play are not frequent but elder children play more fantasy themes than the younger ones. Understanding the significance of play for the development of children we speculate that the educator’s role in supporting or suppressing possibilities for play in the classroom is of greatest importance. Therefore, a more detailed analysis of the teacher’s understanding of the concept and the phenomenon of play would be very meaningful.